Pemberdayaan Peternak Melalui Sosialisasi dan Praktik Pembuatan Mineral Block di Desa Karangkajen, Kecamatan Secang, Kabupaten Magelang - KKN Karangkajen (Fakultas Pertanian_Universitas Tidar, 2025)
The Community Service Program (KKN) conducted in Karangkajen Village, specifically in Diwak and Karangtalun hamlets, aimed to disseminate and demonstrate the making of mineral blocks as feed supplements for goats. The outreach activities included educational presentations and hands-on practice held at the Village Hall, attended by 60 local farmers. The implementation method comprised exploration, preparation, execution, and documentation-evaluation phases. The mineral blocks were formulated using locally available materials such as coarse salt, premix, molasses, rice bran, and white cement. Results showed that goats eagerly licked and consumed the mineral blocks and appeared healthier and more active. High interest among farmers to adopt and independently produce the mineral blocks underscores the potential of this innovation to improve the productivity and health of ruminant livestock, especially in areas with limited forage availability.